Excitatory Modulation of the preBotzinger Complex Inspiratory Rhythm Generating Network by Endogenous Hydrogen Sulfide - Silva, Glauber S. F. da [UNESP]; Sabino, Joao P. J.; Rajani, Vishaal; Alvares, Tucaaue S.; Pagliardini, Silvia; Branco, Luiz G. S.; Funk, Gregory D. (Frontiers Media Sa, 2017)
Hydrogen Sulfide (H2S) is one of three gasotransmitters that modulate excitability in the CNS. Global application of H2S donors or inhibitors of H2S synthesis to the respiratory network has suggested that inspiratory rhythm is modulated by exogenous and endogenous H2S. However, effects have been variable, which may reflect that the RTN/pFRG (retrotrapezoid nucleus, parafacial respiratory group) and the preBotzinger Complex (preBotC, critical for inspiratory rhythm generation) are differentially modulated by exogenous H2S. Importantly, site-specific modulation of respiratory nuclei by H2S means that targeted, rather than global, manipulation of respiratory nuclei is required to understand the role of H2S signaling in respiratory control. Thus, our aim was to test whether endogenous H2S, which is produced by cystathionine-beta-synthase (CBS) in the CNS, acts specifically within the preBotC to modulate inspiratory activity under basal (in vitro/in vivo) and hypoxic conditions (in vivo). Inhibition of endogenous H2S production by bath application of the CBS inhibitor, aminooxyacetic acid (AOAA, 0.1-1.0mM) to rhythmic brainstem spinal cord (BSSC) and medullary slice preparations from newborn rats, or local application of AOAA into the preBotC (slices only) caused a dose-dependent decrease in burst frequency. Unilateral injection of AOAA into the preBotC of anesthetized, paralyzed adult rats decreased basal inspiratory burst frequency, amplitude and ventilatory output. AOAA in vivo did not affect the initial hypoxia-induced (10% O-2, 5 min) increase in ventilatory output, but enhanced the secondary hypoxic respiratory depression. These data suggest that the preBotC inspiratory network receives tonic excitatory modulation from the CBS-H2S system, and that endogenous H2S attenuates the secondary hypoxic respiratory depression.
Keywords: control of breathing; hypoxia; H2S; cystathionine-beta-synthase; AOAA; preBotzinger Complex